Approach to Hemoptysis - Peeva, Magdalena (McGill Journal of Medicine, 2022)
Hemoptysis is the expectoration of blood from the lower airway. A study in the United Kingdom showed that the annual incidence of hemoptysis in primary care is 0.1%. Between 5 and 15% of patients presenting with hemoptysis have a life-threatening hemoptysis Approach to hemoptysis can be particularly perplexing for medical students considering the extensive list of differential diagnosis. It is important for physicians to be able to recognize and manage life-threatening hemoptysis as it is associated with high morbidity and mortality if untreated. Understanding when to further investigate patients at risk of lung cancer can help detect the disease at an earlier stage. This article begins with a brief introduction to life-threatening and nonlife-threatening hemoptysis and provides a detailed discussion of its management including diagnostic approaches followed by appropriate imaging modalities, laboratory findings, and clinical management. The target audience of this article are medical students at their preclinical or clinical phase.